The Influence of Marketing Mix on Generation X and Y Consumer’s Decision-Making Process: A Comparison Study between Café Restaurant and Casual Dining Restaurant in Thonglor - Naruworn Wongwitdecha นฤวร ว่องวิทย์เดชา; Chompunuch Jittithavorn ชมพูนุช จิตติถาวร (Dusit Thani College Journal, 2018)
The objectives of this study were to study the effect of demographic factors on consumer decision-making process, to study the effect of service-marketing mix on consumer decision-making process, and to study the consumer’s decision-making process and consumer’s behavior on purchasing products and services. The scope of the study covers demographic factor, consumer behavior, and marketing mix effecting consumer decision-making process of café restaurant and casual restaurant in Thonglor. Regarding to research methodology, descriptive and inferential statistics were used to describe the population. The research conducted a set of questionnaire to find out the relationship of demographic, consumer behavior, and service marketing mix toward consumer decision-making process. The result showed that most of the respondents were receiving the information about the restaurant through their friend and relative and mainly making the decision based on the influencing of their friends. Moreover, generation Y decision-making process was based on the taste of the foods and the branding of the restaurant, whereas generation X, their decision making process was concern on the price, taste of the foods, and promotion of the restaurant